2023
DOI: 10.1101/2023.07.06.547924
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Integrative spatial analysis reveals a multi-layered organization of glioblastoma

Alissa C. Greenwald,
Noam Galili Darnell,
Rouven Hoefflin
et al.

Abstract: Glioma contains malignant cells in diverse states. Hypoxic regions are associated with a unique histology of pseudopalisading cells, while other regions appear to have limited histological organization, reflecting the diffuse nature of glioma cells. Here, we combine spatial transcriptomics with spatial proteomics and novel computational approaches to define glioma cellular states at high granularity and uncover their organization. We find three prominent modes of cellular organization. First, cells in any give… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 48 publications
2
17
0
Order By: Relevance
“…A vascular niche straddles the hypoxic niche and the inflammatory niche, indicative of vascular proliferation in response to hypoxia and potentially representing an entry point for immune infiltration. These patterns are generally consistent with recent reports 46 .…”
Section: Resultssupporting
confidence: 93%
“…A vascular niche straddles the hypoxic niche and the inflammatory niche, indicative of vascular proliferation in response to hypoxia and potentially representing an entry point for immune infiltration. These patterns are generally consistent with recent reports 46 .…”
Section: Resultssupporting
confidence: 93%
“…The advent of high-throughput spatial transcriptomics methods has led to some important developments in this regard. Early studies using array-based spatial transcriptomics have revealed a changing spatial organization of tumor and immune cells driven by hypoxia 5,10 , and hybridization-based in situ sequencing (HybISS) has helped characterize intercellular interactions of tumor and stromal cells 11,12 . The recurring patterned co-existence of several transcriptional subtypes suggests that tumor cells form a complex system retaining certain functional and organizational aspects of the healthy brain to survive and evolve together with the tumor microenvironment (TME).…”
Section: Introductionmentioning
confidence: 99%
“…Others exhibited gradual accumulation of AC-like markers towards the periphery ( Figure 6F and Figure S4C ). When we analyzed publicly available spatial transcriptomic data from the IVY Glioblastoma Atlas, which was generated from seven spatially distinct regions from 10 adult GBM specimens 48 , we also found that MES markers (NDRG1, CEBPB) were elevated in regions near necrosis, NPC (ELAVL4) and OPC (SOX10) markers were higher toward the infiltrating edge of the tumor, and lamin A/C was lower towards the infiltrating edge ( Figure S4D ).…”
Section: Resultsmentioning
confidence: 91%